The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22317/jcms.v5i3.607
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac induced-acute kidney injury is linked with oxidative stress and pro-inflammatory changes in Sprague Dawley rats

Abstract: Objectives: Diclofenac induces oxidative stress in the body and became the main cause of nephrotoxicity and acute kidney injury (AKI). The traditional markers of AKI are blood urea and serum creatinine which are regarded as low sensitive and low specific in detection the early renal damage. Therefore, the aim of present study was to evaluate oxidative stress and pro-inflammatory   biomarkers in diclofenac induced- AKI in rats. Methods: Twenty   Sprague Dawley Male rat were used and randomly divided in to 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The oxidative stress induced by diclofenac is related to the production of reactive metabolites, 5‐hydroxy diclofenac, and N,5‐dihydroxy diclofenac, which increase the levels of free radicals and result in damage to different tissues. [ 34,38 ] As many cellular and molecular events compromising oxidative stress are fine‐tuned by miRNAs, [ 39 ] our data suggest that miR‐144 is implicated in diclofenac‐induced hepatorenal damage and confirms the notion that oxidative stress is an important player in diclofenac‐triggered hepatorenal injury. On the contrary, miR‐144 was downregulated during protection or treatment with resveratrol.…”
Section: Discussionsupporting
confidence: 78%
“…The oxidative stress induced by diclofenac is related to the production of reactive metabolites, 5‐hydroxy diclofenac, and N,5‐dihydroxy diclofenac, which increase the levels of free radicals and result in damage to different tissues. [ 34,38 ] As many cellular and molecular events compromising oxidative stress are fine‐tuned by miRNAs, [ 39 ] our data suggest that miR‐144 is implicated in diclofenac‐induced hepatorenal damage and confirms the notion that oxidative stress is an important player in diclofenac‐triggered hepatorenal injury. On the contrary, miR‐144 was downregulated during protection or treatment with resveratrol.…”
Section: Discussionsupporting
confidence: 78%
“…This particular aspect highlights the fact that diclofenac may induce AKI via a different primary pathological mechanism. It is postulated that a mechanism related to the induction of oxidative stress and/or reduction of antioxidant capacity may be determinant for diclofenac-induced nephrotoxicity [ 14 , 15 ]. In this sense, investigations have shown that through oxidative stress, increased cytokine release, and nuclear factor κB (NFκB) activation, diclofenac may induce AKI [ 1 , 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tubular cell damage detected in this study was accompanied by inflammatory cells infiltration that invaded into the intertubular tissues to minimize the injury. Similar acute kidney injury has been known to be induced by Diclofenac [30]. Other studies suggest that toxicity of Piroxicam comes about because it acts as a potent chelator of zinc, copper, selenium and manganese -which are the cofactors of the endogenous antioxidant, and because it has a notable negative impact on their scavenging activity [31].…”
Section: Discussionmentioning
confidence: 82%